The Role of Visionary Leadership, Curriculum Innovation, and Management of Educational Resources on the Quality of Character-Based Education for High School Students in West Java - Putu Eddy Purnomo Arta; Heri Setiyawan; Nanny Mayasari (Westscience Press, 2024)
This study examines the influence of visionary leadership, curriculum innovation, and educational resource management on the quality of character-based education in high schools in West Java, Indonesia. Utilizing a quantitative approach, data were collected from 170 high school students through a Likert-scale survey. The data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The findings reveal that curriculum innovation has the most significant positive impact on character-based education, followed by the management of educational resources and visionary leadership. These results underscore the importance of adopting innovative curricula and effectively managing educational resources to enhance character education. Visionary leadership also plays a critical role in setting a direction for character development, though its impact is more pronounced when combined with curriculum and resource management. The study provides insights for educators, policymakers, and school administrators in creating an educational environment that fosters both academic and moral development.